The Clinical Profile of Endoscopically Verified Gastroesophageal Reflux Disease in a Tertiary Care Teaching Hospital: A Cross-Sectional Study - Jain, Dharampaul; Nagpal, Shyam Sunder (Asian Journal of Medical Research, 2020)
Background: Gastroesophageal reflux disease (GERD) is one of the most common gastrointestinal chronic disorders. GERD is described as symptoms or mucosal injury caused by aberrant stomach content reflux into the esophagus or beyond. The normal physiological process of retrograde flow of gastric contents from the stomach to the esophagus is known as gastroesophageal reflux. Subjects and Methods: Total of 87 patients had gastro-esophageal reflux disease as determined by upper gastrointestinal endoscopy. This study comprised patients who had been diagnosed with gastro-esophageal reflux disorder (GERD) after an upper gastrointestinal endoscopy. The upper gastrointestinal endoscopy (UGI scopy) was once thought to be the gold standard diagnostic technique for the diagnosis of gastroesophageal reflux disease. Results: 29 patients (33.3 percent) had no co-morbidities, 39 patients (44.8 percent) had three co-morbidities, and 19 patients (21.8 percent) had three co-morbidities. Heartburn symptoms were nonexistent in 24 patients (27.6%), daily episodes in 17 patients (19.5%), >2 episodes per week in 37 patients (42.5%), and fewer than 2 episodes per week in 9 individuals in the current study (10.3 percent). Regurgitation was nonexistent in 25 patients (28.7%), daily episodes in 15 patients (17.2%), >2 occurrences per week in 23 patients (26.4%), and fewer than 2 episodes per week in 24 patients in our study (27.6 percent). In the study, retrosternal chest pain was not seen in 28 (32.2%) of the 87 GERD patients, daily episodes were seen in 18 (20.7%), >2 episodes per week in 12 (13.8%), and fewer than 2 episodes per week in 29 patients (33.3 percent). Dysphagia was nonexistent in 62 patients (71.3%), daily episodes in 17 patients (19.5%), >2 occurrences per week in 5 patients (5.7%), and fewer than 2 episodes per week in 3 patients in this study (3.4 percent). Conclusion: The prevalence of GERD complications was 29.9%, with the sequence of erosive esophagitis > Barrett’s esophagus > Esophageal stricture. A patient’s age indicates a higher risk of problems. Heartburn, regurgitation, and retrosternal chest pain on a daily basis indicate a higher chance of failing.